EFEKTIVITAS MEDIA SOSIAL INSTAGRAM @TABU.ID SEBAGAI MEDIA PEMENUHAN KEBUTUHAN INFORMASI PENYAKIT MENULAR SEKSUAL PADA MAHASISWA - Harisa Ninda Siti Ramadhany; Marisa Puspita Sary; Maulina Larasati Putri (Institut Pendidikan Tapanuli Selatan, 2023)
In today's modern world, social media plays an important role. Instagram is widely used among Indonesia's active social media audience. The Instagram account @Tabu.id is a source of news and information for Instagram users. This research was conducted in an effort to determine the effectiveness of the social media account Instagram @Tabu.id as a medium for information on sexually transmitted diseases. This study is in the form of a quantitative descriptive survey of 62 students enrolled in Communication Studies at UNJ 2019 and 2020. This study found that the average respondent scored 3.35 on the engagement dimension, 3.34 on the community dimension, 3.28 on the connectedness dimension, 3.18 on the conversational dimension, and 3.14 on the openness dimension. The social media indicator used to share information has the highest average of 3.50%, this indicates that the social media indicator used to share information has the greatest influence on the effectiveness of social media Instagram @Tabu.id as a medium for meeting the information needs of sexually transmitted diseases for 2019 & 2020 UNJ Communication Studies students.